Job Performance and Psychological Well-Being of Thai Hotel Workers: A Multi-Model Path Analytic Study - Raich, Annett; Ho, Robert (Scholar: Human Sciences, 2018)
Job performance and the psychological well-being of employees are of paramount importance for a successful company. Especially in the hospitality industry in a country like Thailand where tourism plays a major role in the growth and sustainment of a healthy Thai economy, it is imperative to identify what and how certain factors may influence job performance and psychological well-being of employees. In order to achieve this aim, the present study posited and investigated a comprehensive process model to determine the direct and indirect influences of the Big Five personality traits of emotional stability, extraversion, openness, agreeableness, and conscientiousness on job performance and psychological well-being among Thai hotel workers, being mediated by their level of stress, burnout, mindfulness, and job satisfaction. A total of 1,512 participants (793 females and 719 males) between 18 and 60 years working in 16 international five-star hotels in Thailand took part in the study. The results revealed that the participants’ Big Five personality traits played major roles in reducing their perceived stress and burnout, increasing their levels of mindfulness and job satisfaction and, subsequently, increasing their job performance and life satisfaction. The study’s limitations, implications, and avenues for further research were discussed.